2012
DOI: 10.5194/tc-6-313-2012
|View full text |Cite
|
Sign up to set email alerts
|

Stable water isotopes of precipitation and firn cores from the northern Antarctic Peninsula region as a proxy for climate reconstruction

Abstract: Abstract. In order to investigate the climate variability in the northern Antarctic Peninsula region, this paper focuses on the relationship between stable isotope content of precipitation and firn, and main meteorological variables (air temperature, relative humidity, sea surface temperature, and sea ice extent). Between 2008 and 2010, we collected precipitation samples and retrieved firn cores from several key sites in this region. We conclude that the deuterium excess oscillation represents a robust indicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 58 publications
5
42
3
Order By: Relevance
“…Thus, this reassures that postdepositional processes in the LCL region are negligible in the time period analyzed and that ice layers likely developed by 20 wind ablation on wind-scouring processes at the plateau. Although these observations are in agreement with the results obtained in this region by Fernandoy et al (2012) and Aristarain et al (1990), several studies (Fernandoy et al, 2012;Simões et al, 2004;Travassos and Simoes, 2004;Jiahong et al, 1998) have identified a significant amount of melt layers in firn cores, mainly from KGI and from the western side of the API at altitudes below 700 m a.s.l. The limited effect of post−depositional processes due to the high accumulation rates and to the ice layers reducing diffusion (Stichler et al, 2001), along with the high 25 correlation between dexcess meteo and dexcess obtained from firn cores, confirm that the isotopic variations observed in firn core isotope records are mostly related to isotopic fractionation occurring during condensation and to rh and SST conditions in the vapor source regions.…”
Section: Stable Water Isotope Fractionation Processes and The Local Tsupporting
confidence: 79%
See 4 more Smart Citations
“…Thus, this reassures that postdepositional processes in the LCL region are negligible in the time period analyzed and that ice layers likely developed by 20 wind ablation on wind-scouring processes at the plateau. Although these observations are in agreement with the results obtained in this region by Fernandoy et al (2012) and Aristarain et al (1990), several studies (Fernandoy et al, 2012;Simões et al, 2004;Travassos and Simoes, 2004;Jiahong et al, 1998) have identified a significant amount of melt layers in firn cores, mainly from KGI and from the western side of the API at altitudes below 700 m a.s.l. The limited effect of post−depositional processes due to the high accumulation rates and to the ice layers reducing diffusion (Stichler et al, 2001), along with the high 25 correlation between dexcess meteo and dexcess obtained from firn cores, confirm that the isotopic variations observed in firn core isotope records are mostly related to isotopic fractionation occurring during condensation and to rh and SST conditions in the vapor source regions.…”
Section: Stable Water Isotope Fractionation Processes and The Local Tsupporting
confidence: 79%
“…More than 200 daily precipitation samples were gathered from O´Higgins Station (57.90°W, 63.32°S, 13 m a.s.l.) during 2008-2009(Fernandoy et al, 2012 and 2014 ( Table 2). Some of these samples were discarded from the analysis due to improper storing.…”
Section: Field Work and Sample Processingmentioning
confidence: 99%
See 3 more Smart Citations